Aanbidding van God in die lig van Bybelse spiritualiteit - De Villiers, PGR (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
Adoration of God in the light of Biblical spirituality This article focuses on adoration as a key motif in New Testament texts in the light of Biblical Spirituality. It firstly discusses the link between adoration and the field of spirituality, and how adoration is given to both God and Christ. After pointing out the individual and collective nature of adoration, adoration is delineated in terms of God’s initiative, whilst attention is then paid to the exclusive adoration of God in the Bible and the mystical presence of God in adoration. In the last part of the essay the development of adoration as worship of Christ is investigated.